"The International Law of the Sea" by Yoshifumi Tanaka - Peruana de Derecho Internacional, Sociedad (2020)
Despite not having passed many years since its first edition, the book “The InternationalLaw of the Sea ”can be considered as a classic in the matter of the Law of the Sea.treatise work reflects Tanaka's encyclopedic knowledge of a branch of lawInternational Public that is constantly evolving and that requires a lot of rigorfor your understanding.